“Just one word, plastic!”: Controversies and caveats in innate lymphoid cell plasticity - Kabil, Ahmed; Shin, Samuel B.; Hughes, Michael R.; McNagny, Kelly M. (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs) are frontline immune effectors involved in the early stages of host defense and maintenance of tissue homeostasis, particularly at mucosal surfaces such as the small intestine, lung, and skin. Canonical ILCs are described as tissue-resident cells that populate peripheral tissues early in life and respond appropriately based on environmental exposure and their anatomical niche and tissue microenvironment. Intriguingly, there are accumulating reports of ILC “plasticity” that note the existence of non-canonical ILCs that exhibit distinct patterns of master transcription factor expression and cytokine production profiles in response to tissue inflammation. Yet this concept of ILC-plasticity is controversial due to several confounding caveats that include, among others, the independent large-scale recruitment of new ILC subsets from distal sites and the local, in situ, differentiation of uncommitted resident precursors. Nevertheless, the ability of ILCs to acquire unique characteristics and adapt to local environmental cues is an attractive paradigm because it would enable the rapid adaptation of innate responses to a wider array of pathogens even in the absence of pre-existing ‘prototypical’ ILC responder subsets. Despite the impressive recent progress in understanding ILC biology, the true contribution of ILC plasticity to tissue homeostasis and disease and how it is regulated remains obscure. Here, we detail current methodologies used to study ILC plasticity in mice and review the mechanisms that drive and regulate functional ILC plasticity in response to polarizing signals in their microenvironment and different cytokine milieus. Finally, we discuss the physiological relevance of ILC plasticity and its implications for potential therapeutics and treatments.